2(3y+4)=3(3y-4)-7y

Simple and best practice solution for 2(3y+4)=3(3y-4)-7y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(3y+4)=3(3y-4)-7y equation:



2(3y+4)=3(3y-4)-7y
We move all terms to the left:
2(3y+4)-(3(3y-4)-7y)=0
We multiply parentheses
6y-(3(3y-4)-7y)+8=0
We calculate terms in parentheses: -(3(3y-4)-7y), so:
3(3y-4)-7y
We add all the numbers together, and all the variables
-7y+3(3y-4)
We multiply parentheses
-7y+9y-12
We add all the numbers together, and all the variables
2y-12
Back to the equation:
-(2y-12)
We get rid of parentheses
6y-2y+12+8=0
We add all the numbers together, and all the variables
4y+20=0
We move all terms containing y to the left, all other terms to the right
4y=-20
y=-20/4
y=-5

See similar equations:

| 3c+-10=8 | | 0.05m+3.95=20 | | 107+x+(180-(11x-3))=180 | | (x+3)3=45 | | 6x+46=124 | | 0.2(20x+15)-9=-0.5(6x-8) | | 107-x+(180-(11x-3))=180 | | 7=3h-11 | | .2a+8=9 | | 1.55x=-2.55 | | x(4x+5)=130 | | 17x+4=18x-5 | | 7-14x=-7 | | x-15.5=17.5 | | 17a/3=-14 | | 2-6=y | | p+84=91 | | w-15=56 | | 6x+12=-5x+12 | | 24=12u | | M=300-10d | | 1/6(9t-8)=t+8/12 | | 6a+11+3a-2+2a=-3a-1+7a+31 | | 5x-18=(2x+12) | | 6(-2g-1)=-(13g+2)6(−2g−1)=−(13g+2 | | 8b+8-4b=b=5 | | 15.5+1.4x=45.5-0.6x | | x/100=60/160 | | -7/2u+5/4=-3/8u=1/4 | | 100-50=5m | | 3(x+4)=7x−4x+5 | | 1+5p-5=-8+3p |

Equations solver categories